(untitled) (Research, Society and Development, 2021)
It has already been demonstrated that climate change can alter the production of renewable energy, being a necessary evaluation regarding the installation of new energy plants. The change in climatic parameters such as maximum and mean temperatures, and cloudiness, can further penalize the semiarid region from social and economic perspectives. Considering this scenario, the projections of climatic parameters can produce approximations of the evolution of their behavior, enabling the delineation of prognostics on the performance of renewable energy production. This study carries out a systematic literature review to verify how climate trends can affect the production of photovoltaic solar energy in semiarid regions. It is concluded that, despite the lack of studies on the subject, the results of scientific and technological research can contribute to minimize the difficult situation of the population living in these regions, providing an improvement in life quality even in adverse climatic situations. The necessity of considering climate trends is highlighted as a prior step to the implementation and optimization of future renewable energy developments on semiarid regions.